Efektifitas Model Pelatihan Outbound Resolusi Konflik dalam Meningkatkan Kemampuan Resolusi Konflik Interpersonal pada Diri Remaja - Ramadhani, Hetti Sari (Persona:Jurnal Psikologi Indonesia, 2015)
This study aimed to test the effectiveness of the model outbound conflict resolution training to improve interpersonal conflict resolution skills in adolescent self . The population was 198 adolescents aged 16-18 years who waitinglist follow the activities of outbound training in TSOT Group Prigen, purposive sampling is done by taking a low score scale resolution of the conflict as much as 30 teenagers who will be divided into two groups: the control group and the experiment group. Calculations made from gainscore value obtained from the pretest and posttest control group and experimental groups with nonparametric statistical Wilcoxon Signed Rank test . Based on the calculation obtained by the Sig . ( 2 tailed) is 0.001 < 0.05 , the obtained results of Ho refused and H1 accepted that there is effectiveness of outbound training model of conflict resolution in improving interpersonal conflict resolution skills in adolescent self.